2012
DOI: 10.1136/archdischild-2011-300920
|View full text |Cite
|
Sign up to set email alerts
|

Lactate as a predictor of mortality in Malawian children with WHO-defined pneumonia

Abstract: Used in conjunction with clinical risk factors and pulse oximetry for measuring oxygen saturation, lactate could play an important role in identifying the sickest patients with pneumonia in developing countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Lactate performed well in risk assessment studies in septic patients; the cut-off values (2 and 4 mmol/L) were quite similar in different reports 12 14 15. Even in children with pneumonia, the risk classification performance of lactate was still reasonably accurate 16. Previous studies have proved the usefulness of lactate in prognosis and risk stratification, but few have investigated its performance in site-of-care decisions in adult pneumonia patients in the ED.…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…Lactate performed well in risk assessment studies in septic patients; the cut-off values (2 and 4 mmol/L) were quite similar in different reports 12 14 15. Even in children with pneumonia, the risk classification performance of lactate was still reasonably accurate 16. Previous studies have proved the usefulness of lactate in prognosis and risk stratification, but few have investigated its performance in site-of-care decisions in adult pneumonia patients in the ED.…”
Section: Introductionmentioning
confidence: 54%
“…In a study conducted in an infectious cohort in the ED, patients with serum lactate of 4 mmol/L or greater had a 3-day mortality rate of 22.4% compared with 1.5% in patients with a serum lactate of 2.4 mmol/L or less 19. A recent study showed that lactate was a robust predictor of death in children with CAP 16. However, studies in adult pneumonia patients are still rare.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of controlled studies demonstrating mortality reduction after bCPAP, the improvement of physiological parameters such as hypoxaemia, a predictor of mortality in children with pneumonia, 21,22 can serve as a proxy indicator for bCPAP effectiveness. In this study there were physiological benefits from bCPAP in a group of children with acute respiratory failure and a high prevalence of HIV: respiratory rates, oxygen saturation and respiratory effort all improved in the hours following initiation of bCPAP.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the publication of a few studies that investigated the association of admission hyperlactatemia with mortality in the pediatric population [6,8-16], information on its importance in a general population of critically ill children is limited [9,14,15]. The predictive value of a single lactate level assessed at admission, unlike serial measurements of lactate, is controversial in the general population of critically ill children [9,14,15].…”
Section: Introductionmentioning
confidence: 99%